Lifetime enhancement in QDLEDs via an electron-blocking hole transport layer - Fatemeh Samaeifar; Mohsen Azadinia; Hany Aziz (Scientific Reports, 2023)
Abstract This study investigates the impact of an engineered hole transport layer (HTL) on the stability of electroluminescent quantum dot light-emitting devices (QDLEDs). The 9-Phenyl-3,6-bis(9-phenyl-9Hcarbazol-3-yl)-9H-carbazole (Tris-PCz) HTL, which possesses a shallower lowest unoccupied molecular orbital (LUMO) energy level compared to the widely used 4,4′-bis(N-carbazolyl)-1,1′-biphenyl (CBP) HTL, is employed to confine electron overflow toward the HTL. Utilizing the Tris-PCz HTL results in a 20× improvement in the electroluminescence half-life (LT50) of QDLEDs compared with conventional QDLEDs using the CBP HTL. Electric and optoelectronic analyses reveal that the migration of excess electrons toward the HTL is impeded by the up-shifted LUMO level of Tris-PCz, contributing to prolonged operational device stability. Furthermore, the augmented electric field at the QD/Tris-PCz interface, due to accumulated electrons, expedites hole injection rates, leading to better charge injection balance and the confinement of the exciton recombination zone within the QD and thus the device stability enhancement. This study highlights the significant influence of the HTL on QDLED stability and represents one of the longest LT50 for a QDLED based on the conventional core/shell QD structure.